Study on hydrophilicity and degradability of chitosan/polylactide-co-polycaprolactone nanofibre blend electrospun membrane. (1st November 2018) - Dorati, R.; Pisani, S.; Maffeis, G.; Conti, B.; Modena, T.; Chiesa, E.; Bruni, G.; Musazzi, U.M.; Genta, I.
Graphical abstract: Highlights: Chitosan was blended to PLA-PCL copolymer. The electrospun nanofibers membranes were fabricated by electrospinning. The blending kept entangled nanofibres structure and stability. The blending improved membrane hydrophilicity and cell attschment and proliferation. Applications can be found either in drug delivery or for tissue regeneration purposes. Abstract: Electrospinning is an interesting technique to produce polymer membranes made of entangled nanofibres. The technique is raising interest in pharmaceutical and biomedical areas. Either electrospun membranes are studied for tissue regeneration purposes, or incorporation of nanoparticles in electrospun membranes can be an opportunity to control the delivery of drug or to obtain dual drug delivery system. In this work suspensions of hydrochloride chitosan salt in copolymer polylactide-co-polycaprolactone (PLA-PCL) solution were electrospun in order to assess an advanced study for developing polymer nanofibre blend membrane loaded with chitosan polymer. The aim of the work was to investigate the properties and stability of chitosan/PLA-PCL electrospun membranes considering their application for tissue regeneration and drug delivery. The electrospun membranes were characterized for their physico-chemical (FT-IR) morphology (SEM) and in vitro biological properties (cytocompatibility and cells engraftment). Results show that homogeneous electrospun PLA-PCL/chitosan blend nanofibres in the range size 800 nm were obtained. Chitosan was loaded inside the nanofibres up to 27.2% (w/w) without modifying nanofibre shape, and only 6% of the loaded chitosan resulted to be on the nanofibre surface. The presence of chitosan in the nanofibres has shown to accelerate the electrospun membranes degradation in vitro .